Content Validation of a Semi-Structured Interview to Analyze the Management of Suffering - Carmen Sánchez-Guardiola Paredes (MDPI AG, 2021)
This work involves the content validation of a semi-structured interview, whose objective is to learn about the management of suffering in people. The interview items have been classified into several categories that define the suffering construct. For the content validation of the instrument, in addition to initially conducting a scientific review on the subject, the procedure known as expert judgement has been used. The results obtained in terms of the content validity achieved in the dimensions and areas assessed are, in general, satisfactory. However, some of these dimensions and certain areas have not exceeded the required minimum values for content validity. Therefore, it is necessary to modify the items comprising these dimensions in the areas evaluated with the additional incorporation of the qualitative suggestions for improvement indicated by the experts. As for agreement among experts, the results point to moderate agreement, which, moreover, is not due to chance.